2020
DOI: 10.1088/1741-2552/aba87d
|View full text |Cite
|
Sign up to set email alerts
|

Physiological synchrony in EEG, electrodermal activity and heart rate reflects shared selective auditory attention

Abstract: Objective. Concurrent changes in physiological signals across multiple listeners (physiological synchrony—PS), as caused by shared affective or cognitive processes, may be a suitable marker of selective attentional focus. We aimed to identify the selective attention of participants based on PS with individuals sharing attention with respect to different stimulus aspects. Approach. We determined PS in electroencephalography (EEG), electrodermal activity (EDA) and electrocardiographic inter-beat interval (IBI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 68 publications
3
53
1
Order By: Relevance
“…In the context of physiological or behavioral signals, this is often referred to as "interpersonal synchronization", and a variety of mechanisms have been hypothesized to be the sources of inter-subject correlation such as social interactions 1 , physical interactions 4,7,21 , shared emotions 9,11 , empathy 22,23 , shared arousal 4,24 , shared attention 25 , and more 1 . The diversity of explanations parallels the diversity of factors known to affect physiological signals.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of physiological or behavioral signals, this is often referred to as "interpersonal synchronization", and a variety of mechanisms have been hypothesized to be the sources of inter-subject correlation such as social interactions 1 , physical interactions 4,7,21 , shared emotions 9,11 , empathy 22,23 , shared arousal 4,24 , shared attention 25 , and more 1 . The diversity of explanations parallels the diversity of factors known to affect physiological signals.…”
Section: Introductionmentioning
confidence: 99%
“…Neural PS was found to be directly proportional to attentional engagement, as strong correlations were found between PS and performance on questionnaires reflective of paid attention (Cohen and Parra, 2016;Cohen et al, 2018;Stuldreher et al, 2020). This directly proportional relationship may thus be used to circumvent supervised learning approaches and the problems that come with such approaches, such as the dependency on labeled training data.…”
Section: Introductionmentioning
confidence: 92%
“…Participants in the stimulus-attending group (SA) were instructed to focus their attention on the interspersed stimuli and ignore the audiobook. In a previous paper on this experiment (Stuldreher et al, 2020), we showed that PS can be used to correctly classify a listener as being instructed to attend to the audiobook or to the sounds. In the current paper, we use PS among individuals in the same group to predict the occurrence of interspersed stimuli over time, for each of the three physiological measures.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The latter may range from indicating where a meeting's attendee is gazing at, to monitoring shared attention through interindividual synchrony in heart rate as recorded through the webcam (cf. Stuldreher et al, 2020). In the context of evaluating consumers' mental state when interacting with systems or products, Consumer Neuroergonomics is especially relevant when mental state is studied over the course of interaction and repeated questioning would influence the mental state of interest itself (Ayaz et al, 2012;Shewokis et al, 2017;Brouwer et al, 2019), or when systematic response biases are expected, e.g., because consumers under study systematically differ in cultural background (Torrico et al, 2018(Torrico et al, , 2019Kaneko et al, in press).…”
Section: Challengesmentioning
confidence: 99%